Midwife in the prevention of preterm birth - Joanna Grzesik-Gąsior; Ewelina Granisz; Agnieszka Bień; Ewa Rzońca (Kazimierz Wielki University, 2017)
Preterm birth is an enormous challenge for the modern obstetrics. Despite the fact that there is a continuous development of prenatal care, the frequency of preterm birth occurrence remains constant. The development of its prophylaxis methods is of utmost interest for many researchers and scholars in Poland and in the world. As a result of multifactorial etiology, the procedure in case of this pathology is vastly difficult and there is no one way, which could effectively eliminate the risk of preterm birth. The most effective way to prevent this kind of pathology, seems to be health promotion and the implementation of prophylaxis methods, not only during the period of pregnancy but also in the pre-pregnancy period. This can be achieved through the education in the field of healthy lifestyle. Health care workers, including midwives, should make every effort to reduce the effects of the preterm birth occurrence. This should be executed by the implementation of the prophylactic methods. The aim of this article is to show the midwife's responsibilities in the prevention of preterm birth at all levels of its prophylaxis.